2017
DOI: 10.1186/s12992-016-0230-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the health impact of transnational corporations: a case study on McDonald’s Australia

Abstract: BackgroundThe practices of transnational corporations affect population health through production methods, shaping social determinants of health, or influencing the regulatory structures governing their activities. There has been limited research on community exposures to TNC policies and practices. Our pilot research used McDonald’s Australia to test methods for assessing the health impacts of one TNC within Australia.MethodsWe adapted existing Health Impact Assessment methods to assess McDonald’s activities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“…For example, in their otherwise thorough framework for conducting corporate health impact assessment Baum and colleagues do not mention how corporations may interfere with the research process and redefine what constitutes scientific evidence for policy making. Neither do they include a measure of how corporations engage in changing the social discourse around the role of the state or the social value of regulation [32, 33]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, in their otherwise thorough framework for conducting corporate health impact assessment Baum and colleagues do not mention how corporations may interfere with the research process and redefine what constitutes scientific evidence for policy making. Neither do they include a measure of how corporations engage in changing the social discourse around the role of the state or the social value of regulation [32, 33]. …”
Section: Introductionmentioning
confidence: 99%
“…This could help executives, for example, to articulate to shareholders why certain public health goals have been pursued above profit margins—an example of which can be seen in the work of Tobacco Free Portfolios. Anaf et al have shown how re-conceptualisations of the nature of business and its impact can be applied practically by developing new systems for performing corporate health impact assessments 20. More needs to be done to promote nuanced approaches to the impact of business on health.…”
Section: Conclusion: Taking the Expanded Inquiry Forwardmentioning
confidence: 99%
“…Chronic diseases are the leading cause of illness, disability and death in Australia, accounting for 90% of all deaths in 2011 12 . The subsequent impacts on health and wellbeing have established the importance of developing an integrated research agenda 6,13 measuring health impacts, 14 and gaining citizen feedback on health impact findings to strengthen impact on policy 15…”
Section: Deliberative Democracy and Citizens’ Juriesmentioning
confidence: 99%
“…The first aim of this paper is to report the outcomes from a citizens’ jury examining the appropriate regulatory responses to a health impact assessment of McDonald's products and operations in Australia 14 . Development of the corporate health impact assessment (CHIA) approach included adapting health impact assessment methodology and applying a framework to identify a range of ways that TNCs in different industry sectors may distally or proximally affect population health and health equity 6 .…”
Section: Deliberative Democracy and Citizens’ Juriesmentioning
confidence: 99%
See 1 more Smart Citation